Analysis of The Development of The Tanjung Kelayang Special Economic Zone in Overcoming Regional Inequality in Bangka Belitung - Sunarya, Iqbal Banyu; Pardede, Kevin Thimoty Natanael (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study examines the role of the Tanjung Kelayang Special Economic Zone (SEZ) in addressing regional inequality in Bangka Belitung Province. Despite contributing to economic growth, with Pangkalpinang's GRDP reaching IDR 11.75 trillion in 2023, investment realization remains low at 3.42% of the IDR 10.3 trillion target. The Williamson Index indicates persistent disparities, recording 0.184 in 2023. Key challenges include inadequate infrastructure, low workforce readiness for tourism, and complex regulations. The study recommends a holistic strategy involving infrastructure development, skills training, regulatory simplification, and support for local MSMEs to ensure equitable benefits. Findings highlight the need for integrated policies to enhance the SEZ's effectiveness in reducing inequality and promoting sustainable development.